Preparation of hydrophobic fabrics and effect of fluorine monomers on surface properties. (November 2019) - Liang, Liping; J Lis Arias, Manuel; Lou, Zixuan; Mao, Qiaole; Ye, Chang; Meng, Xu
Preparation of hydrophobic cotton fabric based on the self-assembly method was proposed. The cotton fabric was modified with 3-(methacryloyloxy)propyltrimethoxysilane and grafted with trifluoroethyl methacrylate and dodecafluoroheptyl methacrylate through free radical polymerization reaction. The objective of this research work was to investigate the effect of fluorine monomer with different chemical structure deposited on cotton fabric on the hydrophobic property. The chemical structure, surface topography, and surface wettability of the fabrics were characterized by Fourier transform infrared spectroscopy, scanning electron microscopy, and water contact angle experiments, respectively. The results showed that the as-prepared fabrics exhibited water contact angle of above 140°. It was noticed that the fluorocarbon chain length of a modifier and its chemical structure could strongly affect the hydrophobic property of the modified fabrics, and the increase in fluorine atoms caused an increase in the water contact angle values.